Examining social capital on mobile SNS: the effect of social support. Issue 4 (6th September 2016) - Zhou, Tao
Abstract : Purpose: The purpose of this paper is to examine the effect of social support on social capital in mobile social networking sites. Design/methodology/approach: Based on the 234 valid responses collected from a survey, structural equation modelling was employed to examine the research model. Findings: The results indicated that social support, which includes informational support and emotional support, has a significant effect on social capital that consists of structural, relational and cognitive capital. Originality/value: Although previous research has found the effect of social capital on user behaviour, it has seldom identified the determinants of social capital. Thus, how to build and develop social capital remains a question. This research examined the effect of social support on social capital.